Amino‐terminated Poly(ethylene glycol) (AT‐PEG) Polymer Hydrogels as Efficient Anionic Dye Adsorbents. Issue 25 (3rd July 2018) - Liu, Yang; Song, Dandan; Song, Shasha; Zhao, Zengdian
Abstract: Polymer hydrogels were obtained by mixing the derivative of terpyridine, 4′‐para‐phenylcarboxyl‐2, 2′:6′, 2′′‐terpyridine (PPCT), and amino‐terminated poly(ethylene glycol) (AT‐PEG) in water. The gelation behaviors, microstructures, rheological properties and application of AT‐PEG/PPCT hydrogels were studied systematically. Microstructures determined by SEM observations demonstrated that the polymer hydrogels were formed by intertwined fibrils. The formation of fibrils was considered to be mainly driven by the electrostatic interaction with the assistance of a delicate balance of various noncovalent interactions, including hydrogen bonding, hydrophobic interaction, van der Waals forces, and etc. The rheological measurements show a strong mechanical strength with an elastic modulus exceeding 5000 Pa and a yield stress exceeding 100 Pa, and which can be regulated by changing the proportion of the gelators. The xerogels exhibited high adsorption efficiency and adsorption capability for the anionic dyes, promised to act as toxic substance adsorbents. Abstract : Polymer hydrogels were obtained by mixing the derivative of terpyridine, 4′‐para‐phenylcarboxyl‐2, 2′:6′, 2′′‐terpyridine (PPCT), and amino‐terminated poly(ethylene glycol) (AT‐PEG) in water. SEM observations demonstrated that the polymer hydrogels were formed by intertwined fibrils. The formation of fibrils was considered to be mainly driven by the electrostatic interaction with the assistance of a delicate balance of various noncovalent interactions, including hydrogen bonding, hydrophobic interaction, van der Waals forces, and etc. The xerogels exhibited high adsorption efficiency and adsorption capability for the anionic dyes.